An eye for an eye - Roop, Peter; Roop, Connie (Lincolnwood, Ill. : Jamestown Publishers, 2000)
In 1775 fourteen-year-old Samantha, who should be wearing dresses, knows that in britches she can out-hunt her twin and out-sail her older brother near their James River home, but can she use those skills against the British when the American Revolution begins?
RS, Savar
Keywords: Siblings -- Fiction; Family life -- Virginia -- Fiction; War -- Fiction; Virginia -- History -- Revolution, 1775-1783 -- Juvenile fiction; Virginia -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; England -- Fiction